Central lymph node changes and progressive massive fibrosis in coalworkers. Issue 7 (July 1986) - Seal, R M; Cockcroft, A; Kung, I; Wagner, J C
Abstract : Lungs from 123 coalworkers coming to necropsy were examined to determine the association between dust related changes in the central lymph nodes and progressive massive fibrosis and secondary foci in the lung parenchyma. Increasingly extensive changes of the central nodes were scored macroscopically, the highest scores indicating erosion through the walls of adjacent bronchi or branches of the pulmonary artery or both. In 88 cases (mainly with extensive changes) microscopic assessment was also made. Increasingly extensive changes of central nodes were associated with the presence of progressive massive fibrosis in the lungs (p less than 0.001) and the presence of secondary foci in lungs without progressive massive fibrosis (p less than 0.03). Microscopic assessments agreed fairly well with macroscopic assessments, but tended to be assigned lower scores. A hypothesis for the pathogenesis of progressive massive fibrosis is proposed whereby dust, accumulating in central lymph nodes, leads eventually to spread through the capsule and rupture into bronchi or pulmonary vessels, thereby sending dust laden activated cells back into the lungs to produce progressive massive fibrosis. These preliminary results are consistent with the hypothesis but more detailed studies are required.